The Role of Hots-Oriented Creative Inquiry Model for Improving Self-Efficacy and Physics Problem-Solving Ability In Gender Perspectives - Distrik, I Wayan; Rosidin, Undang; Abdurraman, Abdurrahman (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to describe the roles of HOTS-oriented creative inquiry learning model in improving self-efficacy and solving problem ability in physics problems to be seen from the gender of senior high school students in Lampung province, Indonesia. This research used the static-group pretest-posttest design. One hundred sixty-five students from five public Senior High Schools in Lampung province, Indonesia, were taken as samples by using random cluster sampling. Problem-solving ability data were obtained from the essay test by using a problem-solving ability survey (PSA), while data of students' self-efficacy level toward physics subjects were collected by using the physics self-efficacy scale (PSES). The percentage of n-gain average determined the improvements of self-efficacy and problem-solving ability, differences between pretest and posttest, and differences between male and female students' abilities were determined by using the Wilcoxon test. The correlation between self-efficacy and problem-solving ability was determined by using Spearman's' coefficient of correlation test. The research result showed that there were significant improvements in self-efficacy and problem-solving ability in physics problems at a significance level of 0.05. The self-efficacy and problem-solving ability of male students were higher than female students. There was a correlation between students' self-efficacy and problem-solving ability in physics.